Computational finance - Lars Stentoft (Journal of Risk and Financial Management, 2020)
The field of computational finance is evolving ever faster. This book collects a number of novel contributions on the use of computational methods and techniques for modelling financial asset prices, returns, and volatility, and on the use of numerical methods for pricing, hedging, and risk management of financial instruments.
Keywords: 330; asset pricing; calibration; derivatives; hedging; multivariate models; risk management; simulation; volatility